Weather Condition Characteristics at the H. Arctowski Station (South Shetlands, Antarctica) for 2006, in Comparison With Multi-Year Research Results - Angiel Piotr J.; Potocki Mariusz; Biszczuk-Jakubowska Julita (Miscellanea Geographica: Regional Studies on Development, 2010)
The maritime Antarctic is characterised by highly variable weather conditions throughout the year, as well as over multi-year periods. The annual variability of weather conditions constitutes an important basis for biological and geographical studies, allowing for the monitoring of the functioning and changes of the geographical environment of the west coast of Admiralty Bay (King George Island, South Shetlands, Antarctica). Year-round meteorological observations (1.2006-12.2006) measured: atmospheric pressure, wind speed and direction, cloud cover, air temperature, relative humidity, total precipitation, snow cover, and Admiralty Bay ice cover.